New Conditions for Testing the Oscillation of Solutions of Second-Order Nonlinear Differential Equations with Damped Term - Asma Al-Jaser; Belgees Qaraad; Higinio Ramos; Stefano Serra-Capizzano (Axioms, 2024)
This paper deals with the oscillatory behavior of solutions of a new class of second-order nonlinear differential equations. In contrast to most of the previous results in the literature, we establish some new criteria that guarantee the oscillation of all solutions of the studied equation without additional restrictions. Our approach improves the standard integral averaging technique to obtain simpler oscillation theorems for new classes of nonlinear differential equations. Two examples are presented to illustrate the importance of our findings.